PERMANENT VASCULAR ACCESS ON THE FOREARM FOR HEMODIALYSIS IN PATIENTS WITH END-STAGE CHRONIC KIDNEY DISEASE - Султанов, Роман Владимирович; Садовский, Александр Андреевич; Мозес, Вадим Гельевич; Мозес, Кира Борисовна; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Центер, Яэль; Кузьменко, Иван Александрович (Medicine in Kuzbass, 2021)
The analysis of the outcomes of 23 surgical interventions for the formation of AV grafts in patients with end-stage chronic renal failure using synthetic prostheses (Venoflow) (n = 10), vascular xenobioprostheses «KemAngioprosthesis» (cattle artery structured with 5 % diepoxide solution, n = 9) and translocated v. saphena magna (n = 4), performed for the period 2018-2021.Installation of AV grafts based on a xenobioprosthesis in patients with end-stage chronic renal failure was associated with a lower incidence of early and late postoperative complications and a higher survival of the vascular access.
Keywords: AV graft; xenobioprosthesis; vascular access